Limitación en Chile de la emigración de las madres custodias junto a sus hijos y/o hijas: ¿una exigencia del principio del interés superior? - Mondaca, Alexis Alberto (2022)
The purpose of this article is to study the limitation that is observed in Chile concerning the possibility of custodial mothers to emigrate. The above, in the cases referring to requests for judicial authorizations about emigration abroad of the referred mothers, which are planned to be carried out in the company of their children and/or daughters. It is stated that such emigratory movements may be the source of a series of benefits from the point of view of the principle of the best interest of the child or adolescent. In addition, it is also stated that the restriction of the aforementioned emigration may cause a violation of the principle of the free development of personality of the custodial mothers. Finally, the possibility of establishing a communication regime with the non-custodial parent which contemplates the use of modern forms of communication is analyzed.